(untitled) - Jansson, Bruce S (Belmont, CA, 2011)
Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Social policy; United States; Social service -- United States; Social policy; Dịch vụ xã hội -- Mỹ (Hoa Kỳ); Chính sách xã hội